Hard surface layer formation on duplex stainless steel using melting and diffusion processes: a review - Paijan, Lailatul Harina; Maleque, Md. Abdul; -, Suryanto (2016)
Duplex stainless steels (DSS) have gained increasing interest in recent years for many industrial applications such as petrochemical process plant, marine engineering and automotive industries. However, this material has experienced lower hardness and poor wear resistance which lead to unanticipated failure in the service. Therefore, development of surface modification could be a vital solution to produce hard protective layer or coating on DSS. The main aim of this work is to brief review on hard surface layer formation on DSS using melting and diffusion processes. Melting technique using tungsten inert gas (TIG) torch and diffusion process using gas nitriding are the effective procesess to meet this requirement. The processing route plays a significant role in developing the hard surface layer for any application with effective cost and environmental factors and careful selection of processing route is very important for surface engineering treatment. In this paper, an attempt is made to review and consolidate the important research works done on melting and diffusion techniques of DSS in the past. The advantages and disadvantages between melting and diffusion technique are presented for better understanding on the feasibility of hard surface formation on DSS. Finally, it can be concluded that this work will open an avenue for further research on the application of the suitable process for hard surface formation on DSS